Divergências doutrinárias e jurisprudenciais sobre a hipótese de perda de mandato parlamentar por condenação criminal transitada em julgado ante a "lei da ficha limpa" - Maia, Anna Thamyres Nunes (2014)
This study examines the development of a participatory democracy as an instrument for achievement of a moralized politics and a principled electoral process. The Complementary Law nº. 135/2010 contributes to the democratic progress, as far as establish new strict and impede ineligibility criteria in defense of administrative probity. Faced with this sociopolitical advancement, we analyze the differences between the hypothesis of loss of parliamentary mandate by judicial sentence of a final decision and the apparent contradiction existing between the arts. 15 and 55, CRFB / 88. Searching for the normative interpretation which is more consistent with constitutional principles, it is noticed that the automatic loss of parliamentary mandate for the crime of high disapproval is the most appropriate solution for the defense of popular sovereignty and legal certainty.